Phage Display Of Naïve Human T-Cell Receptors In Single Chain Format Against Isocitrate Lyase (Icl) And Tumor Necrosis Factor Alpha (Tnfα) - Ch’Ng Chiew Wen, Angela (2024)
T-cell receptors (TCRs) bind with peptide-MHC or lipid-CD1 complexes while antibodies directly bind to antigen. The binding region of T-cell receptors (TCRs) and antibodies exhibit similar three-dimensional (3D) structures. Both composed of two chains and each chain contains two folded domains of one variable and one constant which associate together to create the antigen binding site between them. Since both antibodies and TCR have similar structures, there exists a potential for TCRs to serve as a binding scaffold to bind full protein antigens, much like antibodies. Consequently, the entire experimental study was designed with the aim of investigating whether TCRs can indeed bind to full antigen proteins just like how antibodies bind to antigen proteins. The recognition site of the TCR comprises of the alpha and beta variable regions. Consequently, both alpha and beta variable regions are interconnected through a glycine-serine linker, resulting in the formation of a single-chain TCR. Additionally, a naïve scTCR library was meticulously crafted using phage display technology with a library size of 1010. Then, the scTCR library was used to isolate scTCR binders against two designated antigens recombinant isocitrate lyase (rICL) and recombinant tumor necrosis factor alpha (rTNFα). A total of three monoclonal scTCR binders to rICL and two to rTNFα respectively were isolated. All of the human antibody constant (CH1 or CK) scTCR fusion proteins expressed best at 30 °C except a-rICL-2G10 scTCR.